Analisis Pelaksanaan Dan Pengelolaan Perpajakan Di Kecamatan Pangkalan Kerinci, Kabupaten Pelalawan - Ardinata, Kaisar Rezky; Marta, Fitri Yul Dewi (Jurnal Ilmiah Wahana Pendidikan, 2026)
This study aims to analyze the implementation of tax administration and the level of taxpayer compliance in the working area of the Primary Tax Office (KPP) of Pangkalan Kerinci, as well as to identify the challenges and opportunities in tax management faced by the institution. This research uses a qualitative approach with a descriptive method, where data is collected through literature studies, documentation, and observation of programs and activities carried out by KPP Pratama Pangkalan Kerinci. The results show that the tax office has implemented various initiatives to improve the efficiency and effectiveness of tax services, such as the "Jempol Pajak" program, tax education through social media, and collaboration with local governments. The compliance rate of individual taxpayers shows a positive trend, with the annual tax return (SPT) reporting target exceeding 100% in 2020. However, there are still significant challenges, such as the lack of public understanding regarding tax obligations and technical difficulties in implementing the newly introduced Coretax administrative system. On the other hand, the use of information technology, the increase in digital literacy among citizens, and cross-sectoral collaboration present great opportunities to enhance the sustainability of the tax system. This study recommends the improvement of more inclusive tax education programs and the strengthening of synergy between tax authorities and local governments to create a more effective and equitable tax system.